1983
DOI: 10.1042/bj2130437
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the major endoglucanase from Aspergillus fumigatus Fresenius

Abstract: Aspergillus fumigatus (Fresenius), IMI 246651, A.T.C.C. 46324, produces two beta-glucosidase enzymes, cotton-solubilizing activity, xylanase and endoglucanase enzymes which can be separated by gel-filtration chromatography. The major endoglucanase does not bind to concanavalin A-Sepharose and does not stain with periodic acid/Schiff reagent. It is homogeneous on polyacrylamide isoelectric focusing (pI = 7.1) and has a mol.wt. of 12500 by sodium dodecyl sulphate/polyacrylamide-gel electrophoresis. The endogluca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 24 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…4b). These results suggest that our enzyme was stable up to 60°C and above this temperature; a rapid decrease in stability takes place particularly after incubation for 1 h. On the other hand, endoglucanase from A. niger (Parry et al 1983) and Bacillus strains CH43 and HR68 (Mawadza et al 2000) was reported to be stable up to 50°C.…”
Section: Effect Of Temperature On Enzyme Activity and Stabilitymentioning
confidence: 77%
“…4b). These results suggest that our enzyme was stable up to 60°C and above this temperature; a rapid decrease in stability takes place particularly after incubation for 1 h. On the other hand, endoglucanase from A. niger (Parry et al 1983) and Bacillus strains CH43 and HR68 (Mawadza et al 2000) was reported to be stable up to 50°C.…”
Section: Effect Of Temperature On Enzyme Activity and Stabilitymentioning
confidence: 77%
“…Aspergillus sp. is known to produce a variety of cellulolytic enzymes including endo-β-1,4-glucanase or CMCase [31,36,37]. In the present work, different trials were conducted to purify the crude EG produced by A. terreus DSM 826.…”
Section: Discussionmentioning
confidence: 99%
“…A maximum decrease of the enzyme activity was recorded when heating the enzyme at 90°C for 30 min. Endoglucanase from A. fumigatus was reported to be stable at 50°C (Parry et al, 1983). This comparison shows that the heat stability of CMCase from A. oryzae is higher than that of the enzyme mention previously.…”
Section: Thermal Stabilitymentioning
confidence: 65%
“…The optimal pH for endoglucanase from Aspergillus niger was found to be 6.0 to 7.0 (Parry et al, 1983). Akiba et al (1995) reported that cellulase production was high at pH 4.0 and pH 4.5 by A. niger.…”
Section: Effect Of Ph On the Production Of Cellulolytic Enzymesmentioning
confidence: 99%